Pengaplikasian Metode Projected Unit Credit tipe Constant Dollar dan Attained Age Normal dalam Perhitungan Dana Pensiun - Regina Hanna Prameswari; Poetry Priliantika; Lukita Ambarwati; Dwi Wiraningsih, Eti (Mathematics Study Program, Faculty of Mathematics and Natural Science, Universitas Negeri Jakarta, 2024)
This research aims to calculate pension fund program by using Projected Unit Credit (PUC) Method Constant Dollar Type and Attained Age Normal (AAN) Method. The differences analysis between PUC Method Constant Dollar Type and AAN Method shows that PUC Method Constant Dollar Type has a smaller final value of normalized contribution financing for the same pension benefit. Thus, for actuarial liabilities PUC Method Constant Dollar Type has a higher value compared to AAN Method. The result shows that PUC Method Constant Dollar Type is more beneficial for participants with a smaller final value of normal contribution financing, while AAN Method is more beneficial for pension fund with higher final value of normal contribution financing.